Dynamic Villages in the Hinterland of a Polycentric Region: Case Study of the Górnośląsko-Zagłębiowska Metropolis in Poland - Elżbieta Zuzańska-Żyśko; Marlena Dyszy (Land, 2021)
This article examines the growth of the labour market and entrepreneurship in a metropolitan area. In particular, the study attempts to answer how the economy of the rural regions is developing in the hinterland of a large urban complex in Southern Poland, which is transforming from a post-industrial conurbation into a metropolitan area. The study applied Florence’s local specialization index, statistical measures, dynamics indexes, and Pearson’s correlation index. The research results show that the local economy, including the labour market, is systematically growing. Rural communes refer to multifunctional development based on services, and they represent diverse economic specializations. They are subject to economies of scale and benefit from the proximity and impact of a large urban complex. The economic growth of rural areas in the hinterland is related to entrepreneurship, convenient location in relation to cities, and migration from cities to villages.